2015
DOI: 10.1002/ana.24391
|View full text |Cite
|
Sign up to set email alerts
|

Atypical functional brain connectivity during rest in autism spectrum disorders

Abstract: Differences in functional connectivity may suggest the presence of neural atypicalities that impact the development of typical connectivity in ASD. In addition to affecting DMN dynamics, these atypicalities may also impact social-cognitive abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 47 publications
9
68
1
Order By: Relevance
“…Many studies have reported decreased FC between DMN regions in those with ASD (Assaf et al, 2010;Kennedy & Courchesne, 2008;Monk et al, 2009;Weng et al, 2010), although hyperconnectivity within this network has also been reported (Monk et al, 2009;Uddin et al, 2013a). One study found that hypo-or hyperconnectivity of the DMN may be region-specific (Doyle-Thomas et al, 2015). Increased FC in the occipital network is consistent with previous findings of increased local connectivity in primary visual regions (Keown et al, 2013) and increased involvement of extrastriate cortex (Shen et al, 2012) in ASD.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the supporting
confidence: 84%
“…Many studies have reported decreased FC between DMN regions in those with ASD (Assaf et al, 2010;Kennedy & Courchesne, 2008;Monk et al, 2009;Weng et al, 2010), although hyperconnectivity within this network has also been reported (Monk et al, 2009;Uddin et al, 2013a). One study found that hypo-or hyperconnectivity of the DMN may be region-specific (Doyle-Thomas et al, 2015). Increased FC in the occipital network is consistent with previous findings of increased local connectivity in primary visual regions (Keown et al, 2013) and increased involvement of extrastriate cortex (Shen et al, 2012) in ASD.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the supporting
confidence: 84%
“…12 Reduced DMN RS connectivity has been observed across age-groups in individuals with ASD, both within the DMN [13][14][15][16] and between the DMN and other regions. [17][18][19][20] In contrast, some studies have reported increased DMN RS connectivity. 13,[20][21][22] Reduced SN RS connectivity has been found in children, adolescents and adults with ASD, affecting connectivity within the SN as well as connectivity between SN key nodes and sensory, prefrontal, and emotion processing regions.…”
Section: Introductionmentioning
confidence: 93%
“…Because ASD presents in early childhood and brain connectivity changes with age (Doyle- Thomas et al 2015), the studies were performed serially in developing rats from P18 -P25. These ages would be human equivalent age of 5 to 6 yr (Clancy et al 2007;Workman et al 2013).…”
Section: Altered E/i Balance and Connectivitymentioning
confidence: 99%
“…It is important to note that ASD is an evolving disorder and, like changes in regional brain volume Lange et al 2015), brain connectivity changes with age (Cheng et al 2010;Doyle-Thomas et al 2015). Therefore, it is extremely important that age and developmental stage be accounted for when evaluating functional connectivity in ASD.…”
Section: Aberrant Connectivity In Autismmentioning
confidence: 99%
See 1 more Smart Citation